An experimental investigation on the noise emission and fuel consumption of diesel engine - Foo, Jin Yuan (2014)
Road traffic has always been a source of noise pollution owing to the rapid advancement in technology and growing population. This problem seems to be more dominant especially in developing countries that do not have proper statistical information to generate noise estimates for noise management regulations. Intense or repeated exposure to loud noise may cause hearing impairment. There is no cure for one suffering from hearing impairment. With the benefits that diesel engines bring, it has become a common alternative source of automotive power. However, one of the banes of diesel engine is that it produces more noise than a normal gasoline engine. This can pose a potential threat to people such as commercial vehicle operators who are often exposed to this harmful noise over a long period of time. Hence, this project studies the effect of mineral and synthetic engine oil on diesel engine noise and fuel consumption rate. Later phase involves the use of STP fuel additive to investigate the effects. From this study, it is found that synthetic engine oil contributes to a better engine performance than mineral oil in terms of noise emitted and fuel consumed. Using synthetic engine oil, it can offer a noise reduction of 2 to 3 dB at lower engine load and speed and a reduction of 4 to 5 dB at higher engine load and speed. Fuel consumption rate is also greatly improved at higher engine speed. However, STP fuel additive showed close to negligible effect on engine noise emission but displayed great improvement in fuel consumption rate at high engine speed. Hence, the effect of noise emission is not correlated to fuel consumption. With the use of synthetic engine oil and fuel additives, it can bring about significant improvement in engine performance in terms of noise emission and fuel consumption.